STRATEGI DEWAN PIMPINAN DAERAH II PARTAI GOLONGAN KARYA PADA PEMILIHAN UMUM LEGISLATIF DI KABUPATEN SIAK TAHUN 2014 - Eko Andriyanto; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study examines the Golkar Party victory in legislative elections in Siak 2014 and are the focus of this research is what strategy the Regional Leadership Council II Golkar Party to win the election. The focus of this research is the influence of regents to win the election in 2014. In this study, the use of qualitative methods for descriptive analysis of the data presented in the form of qualitative portrait of the real situation in detail and the actual look at the problem and research objectives. This study using purposive sampling and interviewing informants as information objects that aims to achieve the goal to get the information in this study. Data used in this study are primary data and secondary data.The results showed in making the strategy undertaken by the leadership of the Regional Council II Golkar Party in legislative elections in Siak 2014, there are several strategies undertaken by the Regional Executive Council II Golkar Party of which recruit potential legislative candidates won the election, forming network Success Team in each district, featuring issues appropriate to their own desires to the community, district head in the direction of Regents of the Golkar Party.Keywords: Strategy, Political Party, Golkar